2020
DOI: 10.1186/s40738-020-00092-1
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors for intrauterine insemination outcomes: a review

Abstract: Purpose Intrauterine insemination (IUI) is a frequently utilized method of assisted reproduction for patients with mild male factor infertility, anovulation, endometriosis, and unexplained infertility. The purpose of this review is to discuss factors that affect IUI outcomes, including infertility diagnosis, semen parameters, and stimulation regimens. Methods We reviewed the published literature to evaluate how patient and cycle specific factors af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
1
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 99 publications
1
21
1
3
Order By: Relevance
“…Many authors have confirmed the importance of sperm quality, exposing a total motile sperm count above 5 × 10 6 to be suitable for the procedure. Nevertheless, in addition to all known prognostic factors, we still lack methods to optimally select suitable patients and are therefore unable to significantly improve the outcomes [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Many authors have confirmed the importance of sperm quality, exposing a total motile sperm count above 5 × 10 6 to be suitable for the procedure. Nevertheless, in addition to all known prognostic factors, we still lack methods to optimally select suitable patients and are therefore unable to significantly improve the outcomes [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The composition of seminal fluid from different men differs in makeup across a number of analytes [14]. While not completely understood, the reasons for these differences may be linked to differences in donor genetics, diet, and activity level prior to sample delivery [15,16]. Furthermore, discrepancies between samples provided by the same donor on a different day or time of day have been noted.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these test results, the inclusion criteria of our study were made as follows: female age <40 years, CD 3 FSH <10 mIU/ml, patent fallopian tubes and a normal uterine cavity according to hysteroscopy, and a male partner with a total sperm concentration of >10 million sperm/ml, a total post-wash sperm count>2 million, and a normal morphology ≥4% ( 11 ). In addition, only patients who had one of the following infertility causes were included: ovulatory dysfunction, unexplained factors, mild male factors, and sexual dysfunction.…”
Section: Methodsmentioning
confidence: 99%